1996
DOI: 10.1099/0022-1317-77-3-413
|View full text |Cite
|
Sign up to set email alerts
|

Sequence analysis of the S1 glycoprotein of infectious bronchitis viruses: identification of a novel genotypic group in Australia

Abstract: Sequencing of the S1 genes of nine Australian strains of infectious bronchitis virus (IBV) identified two genotypically distinct groups of strains. The strains Vic S, V5/90, N1/62, N3/62, N9/74 and N2/75 comprised group I, sharing 80.7-98-3 % identity in their deduced amino acid sequences. All group I strains were able to replicate in the trachea and kidney but only four strains, Vic S, N1/62, N9/74 and N2/75, were nephropathogenic, the latter three causing mortalities ranging from 32 to 96%. Group II containe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
63
1
3

Year Published

2004
2004
2014
2014

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(69 citation statements)
references
References 19 publications
2
63
1
3
Order By: Relevance
“…Strains Vic S, S and I belong to the same serotype (B) by virus neutralization, and also to the same type by monoclonal antibody typing, while strain Armidale belongs to a different serotype (C) (Ignjatovic & McWaters, 1991). Six Australian reference strains, N3/62, V2/71, Q1/73, N2/75, N1/88 (Ignjatovic & McWaters, 1991) and V5/90 (Sapats et al , 1996) (Wadey & Faragher, 1981;Ignjatovic & McWaters, 1991;Ignjatovic et al, 2002).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Strains Vic S, S and I belong to the same serotype (B) by virus neutralization, and also to the same type by monoclonal antibody typing, while strain Armidale belongs to a different serotype (C) (Ignjatovic & McWaters, 1991). Six Australian reference strains, N3/62, V2/71, Q1/73, N2/75, N1/88 (Ignjatovic & McWaters, 1991) and V5/90 (Sapats et al , 1996) (Wadey & Faragher, 1981;Ignjatovic & McWaters, 1991;Ignjatovic et al, 2002).…”
Section: Methodsmentioning
confidence: 99%
“…Traditionally, IBV serotypes have been identified using virus neutralization or haemagglutination inhibition tests. Monoclonal antibodies, oligonucleotide fingerprinting and sequencing have also been used to type IBV isolates (Ignjatovic & McWaters, 1991;Cavanagh et al, 1992b;Kwon et al, 1993;Sapats et al, 1996). However, all these methods are labour intensive, expensive, time consuming, and require isolation and culture of viruses (Kwon et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Homology search showed that the S1 protein sequences of strains JP8127, JP8443 and JP9758 were most closely related to that of an Australia field strain designated as N1-62 [8], whereas the S1 protein sequence of TW97-4 was most similar to that of a Taiwanese field strain designated as A1211 [11]. A phylogenetic tree was constructed by using the S1 protein sequences (Fig.…”
mentioning
confidence: 99%
“…1). In this tree, strains JP8127, JP8443 and JP9758 fell into the branch containing viruses isolated from Australia [8], New Zealand and California [7] (Fig. 1).…”
mentioning
confidence: 99%
“…SimPlot analysis examines relationships between nucleotide sequences at a set incremental level to provide a more accurate representation of the relationship between strains than using identity scores to compare entire stretches of genomic sequence. A point of crossover between the similarity plots indicates a shift from a high identity to a low identity (or vice versa), and therefore indicates a potential point of recombination (Lole et al, 1999 (Wadey & Faragher, 1981;Sapats et al, 1996;Ignjatovic et al, 2006;Mardani et al, 2006aMardani et al, , 2008Mardani et al, , 2010. The vaccine strains included in these analyses were Armidale, VicS and S (Wadey & Faragher, 1981).…”
Section: Methodsmentioning
confidence: 99%